Peningkatan Kualitas Usaha Makanan Ringan Di Desa Gamping Tengah, Krian, Sidoarjo - Desrina Yusi Irawati; Agrienta Bellanov; Armadeo Ruben Canariesa; Cornelis Tredick Putra Pratama (Randang Tana - Jurnal Pengabdian Masyarakat, 2024)
Gamping Village is a village in the Krian area, Sidoarjo, which is a busy route between cities. Several housewives there have businesses to support the family economy. One of the food businesses managed by Gamping village housewives is the "4W" brand snack business. The types of food produced are elephant ears, hidden beans, onion sticks and mini pastels. Based on real conditions, "4W" snacks have disadvantages, namely that the product easily "goes sour", the packaging is still simple, and it does not come with a label. The aim of this community service is to achieve quality products with attractive product packaging and label designs, as well as minimal oil products. The methods of community service activities are discussion, counseling and mentoring. The initial discussion was carried out with a direct visit to explore the problems and the agreement program being implemented. The counseling was attended by Central Gamping women who own snack businesses. As an example of developing quality food products, a mentoring program was carried out in one of the snack brands, namely the "4W" product. The program carried out on the "4W" product is the development of a simple spinner to reduce oil content so that the product life is longer. The “4W” product packaging was also changed to use a zippered standing pouch. The product is more attractive, easy to open and close, and practical to carry anywhere. Packaging becomes more informative with the addition of new labels. All service activities ran smoothly, supported by Central Gamping women and "4W" product owners